1992
DOI: 10.1007/bf01321341
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of children with serious emotional disturbance served in residential and school settings

Abstract: The National Adolescent and Child Treatment Study (NACTS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 13 publications
3
39
0
Order By: Relevance
“…In addition, to be part of the study, a child or youth had to have required services from two or more service agencies or systems. A brief consideration of data from selected surveys of young people with EBD (Kelleher, Hohmann, & Windle, 1989;Silver, 1989;Zeigler-Dendy, 1989) and o t h e r system-of-care projects (Hawkins, Almeida, & Samet, 1989;Moore, 1991) provides some context for the present findings. Kelleher et al studied a representative national sample of child and adolescent users of community mental health centers during the earjy 1980s.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, to be part of the study, a child or youth had to have required services from two or more service agencies or systems. A brief consideration of data from selected surveys of young people with EBD (Kelleher, Hohmann, & Windle, 1989;Silver, 1989;Zeigler-Dendy, 1989) and o t h e r system-of-care projects (Hawkins, Almeida, & Samet, 1989;Moore, 1991) provides some context for the present findings. Kelleher et al studied a representative national sample of child and adolescent users of community mental health centers during the earjy 1980s.…”
Section: Discussionmentioning
confidence: 95%
“…The average age of subjects in Kelleher et al (1989) was similar to that of the present sample, even though they included quite a few children in the 5-to 10-year-old range. Silver's (1989) sample averaged nearly 14 years of age. In Hawkins et al (1989) and Moore (1991), the participants had a mean age of about 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research conducted on children with ADHD in residential care report prevalence estimates of ADHD within a residential sample. For example, when evaluating children with serious emotional disturbance, Silver et al (1992) found a higher prevalence of ADHD in a residential treatment sample (16%) than in a school sample (8%). Other studies (Connor et al 2004;Fields et al 2006;Pugh et al 1997) report 40-92% of children in residential care present ADHD symptoms.…”
Section: Introductionmentioning
confidence: 94%
“…For example, children in residential care are often reported to have elevated levels of underachievement in school , and demonstrate high rates of grade retention, drop-out, and overall school failure (Wurtele et al 1983). Behaviorally, these children frequently demonstrate high levels of aggression, poor impulse control, delinquency, conduct disorder, depression, and anxiety (Connor et al 2004;Greenbaum et al 1996; Moore and O'Connor 1991;Quinn and Epstein 1998;Silver et al 1992). Finally, children in care often experience multiple out-ofhome placements, are victims of physical and sexual abuse or neglect, and come from impoverished homes with greater family dysfunction (Connor et al 2004;CWLA 2005;Wells and Whittington 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Most studies conducted among these youth describe the host of behavioural and emotional problems that they have (Landsverk et al 2009;Polnay et al 1996;Silver et al 1992;Whitaker et al 1998), but fail to connect these problems to actual trauma by documenting them through trauma-specific research or measures. Indeed, although there is an increasing awareness of the probable high rates of trauma exposure in the histories of youth in out-of-home care, thus far only a few studies have addressed this issue.…”
mentioning
confidence: 96%